Computer-Visualized Sound Parameter Analysis Method and Its Application in Vocal Music Teaching - Zhenming Yu (Advances in Multimedia)
In order to improve the quality of vocal music teaching, this paper applies the computer visualization sound parameter analysis method to vocal music teaching and discusses the scheme of parametric coding. Moreover, this paper adopts the transient signal detection mechanism to divide the signal. For frames that have detected a shock signal, frequency-domain parametric differential predictive coding can be used like temporal noise shaping (TNS) techniques. In addition, based on the short-term periodicity and short-term stationarity of speech signals, an analytical synthesis model based on harmonic decomposition is proposed. Through the simulation data analysis, it can be seen that the computer visualization sound parameter analysis method proposed in this paper has a very good application effect in vocal music teaching and can improve the quality of vocal music teaching.